Adaptação fonológica de nomes próprios de origem estrangeira: comparação entre português arcaico e português brasileiro - Massini-Cagliari, Gladis [UNESP] (2011)
This paper aims to discuss the phonological adaptation of proper nouns of foreign origin in two moments of the language temporal continuum: Archaic and Brazilian Portuguese.